2011
DOI: 10.3356/jrr-11-21.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Falconid Mummies from the Late Period of Ancient Egypt Using Noninvasive Techniques

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…The bird of prey mummy (W531) is wrapped and covered in a black, possibly resinous, material. It is believed to be votive, consistent with other studies of similar bird mummies 5 . The specimen is 23 cm long and 7 cm wide at its broadest point near the midpoint.…”
Section: Bird Of Prey (W531)supporting
confidence: 90%
See 2 more Smart Citations
“…The bird of prey mummy (W531) is wrapped and covered in a black, possibly resinous, material. It is believed to be votive, consistent with other studies of similar bird mummies 5 . The specimen is 23 cm long and 7 cm wide at its broadest point near the midpoint.…”
Section: Bird Of Prey (W531)supporting
confidence: 90%
“…However, microCT permits the measurement of bone elements in the correct plane, enabling us to identify the likely species of the mummy as a kestrel. Previous studies have shown that falcons has been found in mummified packages 5,13 , and birds of prey feature heavily in ancient Egyptian religion, although the exact species is not always identified by Egyptologists. Birds of prey are usually associated with solar gods, for example the gods Horus, Sokar, and Re.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, made more accessible by the trivialization of new medical imaging technologies, research on the study of animal mummies is becoming more and more important internationally (cf. [1], [14], [19], [31], [27], [30], [32], [8], [35], [15], [40], [13], [18], [42]).…”
Section: Introductionmentioning
confidence: 99%
“…The use of CT scanning for the analysis of mummies has even become a gold-standard method (Rühli et al, 2004;Chhem, 2006). A number of animal mummies have also been analysed using CT scanning, including (among others) birds of prey, cats and ibises (Falke et al, 1987;Ikram, 1995;Jackowski et al, 2008;Morgan and McGovern-Huffman, 2008;McKnight, 2010;McKnight et al, 2011;Morgan et al, 2011;Bailleul-LeSeur, 2012;Cornelius et al, 2012;Gnudi et al, 2012;Wade et al, 2012).…”
Section: Introductionmentioning
confidence: 99%